Diltiazem Increases the Liver Regeneration in Rats by Inhibiting TGF-β1 - Ozsay, Oguzhan; Ozer, Ilter; Bostanci, Erdal Birol; Sumer, Fatih; Cayci, Murat; Karaman, Kerem; Akoglu, Musa; Sert, Ismail (European Scientific Journal, ESJ, 2019)
Transforming growth factor beta-1 (TGF- β1) is the most important inhibitory cytokine during the hepatic regeneration process. Diltiazem is a Ltype calcium channel blocker that has inhibitory effect on TGF- β1. The aim of the present study was to determine the effect of diltiazem on hepatic regeneration. Sixty female Wistar Albino rats were used. Three groups were created; the control, low dose diltiazem and high dose diltiazem groups, each consisting of 20 rats. After partial liver resection (70% hepatectomy), saline was introduced to control group, 5 mg/kg diltiazem was introduced to low dose group and 15 mg/kg diltiazem to high dose group intraperitoneally. Ten rats in each group were sacrificed on the first postoperative day and the remaining rats on the fifth day. Liver weight, mitotic rate and the Ki-67 ratio were measured for determining hepatic regeneration. Liver regeneration rate on the fifth postoperative day was significantly higher both in the low dose and high dose diltiazem groups than the control group (Low diltiazem vs control: P<0.001; High diltiazem vs control: P<0.001). No significant difference was found between the groups regarding the number of mitoses on the first and fifth days following partial hepatectomy (P>0.05). The Ki-67 ratio on the first postoperative day was significantly higher both in the low dose and high dose diltiazem groups than the control group (Low diltiazem vs control: P<0.001; High diltiazem vs control: P<0.001). Diltiazem increases liver regeneration by inhibiting TGF-β1.